The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/jmri.24550
|View full text |Cite
|
Sign up to set email alerts
|

White matter lesion load is associated with resting state functional MRI activity and amyloid pet but not FDG in mild cognitive impairment and early alzheimer's disease patients

Abstract: Purpose To quantify and investigate the interactions between multimodal MRI/positron emission tomography (PET) imaging metrics in elderly patients with early Alzheimer's disease (AD), mild cognitive impairment (MCI) and healthy controls. Materials and Methods Thirteen early AD, 17 MCI patients, and 14 age-matched healthy aging controls from the Alzheimer's Disease Neuroimaging Initiative database were selected based on availability of data. Default mode network (DMN) functional connectivity and fractional am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 42 publications
8
48
0
1
Order By: Relevance
“…However, the results from these studies are inconsistent. For example, while most studies observed a decrease in the DMN and MTL connectivity of an MCI patient , others found an opposite result . Additionally, the previous studies failed to provide significant information to diagnose MCI .…”
Section: Introductionmentioning
confidence: 96%
“…However, the results from these studies are inconsistent. For example, while most studies observed a decrease in the DMN and MTL connectivity of an MCI patient , others found an opposite result . Additionally, the previous studies failed to provide significant information to diagnose MCI .…”
Section: Introductionmentioning
confidence: 96%
“…Similarly, the reduction of ACC and/or PCC’s FC with other regions (e.g., precuneus, hippocampus, middle temporal lobe) has been consistently revealed in individuals with amnestic mild cognitive impairment (MCI) compared to their cognitively normal controls (Bai et al, 2009; Binnewijzend et al, 2012; Dunn et al, 2014; Tam et al, 2015; Yan, Zhang, Chen, Wang, & Liu, 2013), and differentiates individuals with amnestic MCI from MCI due to deficits unrelated to AD (Dunn et al, 2014). However, the relationships between FC and cerebral amyloid deposition have been varied across studies of cognitively normal older adults or MCI (Chao et al, 2013; Hedden et al, 2009; Lim et al, 2014; Mormino et al, 2011; Sheline et al, 2010; Sperling et al, 2009; Zhou, Yu, & Duong, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…When functional connectivity maps were derived for each group separately, the addition of WMSA as a regressor minimally altered the functional connectivity profile in the control group, although drastically decreased mPFC functional connectivity strength in those with MCI. Greater white matter lesion burden has been previously associated with impaired resting state brain connectivity within medial frontal regions in those with MCI (Zhou et al, ), and tract‐specific white matter damage subserving then mPFC has been related to functional connectivity disruption in patients across the continuum of AD (Taylor et al, ; Tullberg et al, ). Although WMSA are not specific to AD pathology, our prior work has shown that the regional distribution of WMSA lesions may be a critical component of AD development and progression given that regions showing a statistically significant relationship between WMSA and time‐to‐AD‐conversion are limited to the temporal and the frontal white matter (Lindemer et al, ).…”
Section: Discussionmentioning
confidence: 99%